Gayo Buffalo Maintenance Management Viewed from the Technical Aspect of Maintenance in Gayo Lues Regency - Zikri Maulina Gaznur; Budi Afriandi; Hendra Koesmara (Agricultural Faculty, 2022)
ABSTRACT. Gayo Lues Regency, Aceh Province is a very potential area for the development of buffalo. This study aims to determine the application of technical aspects of buffalo breeding in Gayo Lues which is expected to be a reference for local governments regarding genetic quality improvement of Gayo buffalo conservation programs to maintain population growth of one of the national germplasms. This research was conducted in Gayo Lues Regency covering two sub-districts, Blangkejeren and Dabun Gelang. This study uses a qualitative method by conducting a simple random sampling survey of 54 buffalo farmers. The number of samples was determined by the Slovin formula, the criteria for breeders to maintain at least 5 buffaloes. The research data is processed by calculating the percentage and then compared with the standard by Minister of Agriculture Regulation (2006). The results showed that the score of the application of the technical aspects of keeping buffaloes obtained in Gayo Lues was 55.96% including the application of the technical aspects of breeding and reproduction 62.39%, food 41.47%, maintenance management 57.20%, health 61, 71% and housing 73.40%. It can be concluded that the implementation of technical aspects of buffalo maintenance in Gayo Lues Regency is still not good enough.(Manajemen pemeliharaan kerbau Gayo ditinjau dari aspek teknis pemeliharaan di Kabupaten Gayo Lues)ABSTRAK. Kabupaten Gayo Lues, Provinsi Aceh merupakan wilayah yang sangat potensial untuk pengembangan ternak kerbau. Penelitian ini bertujuan untuk mengetahui penerapan aspek teknis pemeliharaan ternak kerbau di Kabupaten Gayo Lues yang diharapkan bisa menjadi acuan pemerintah daerah mengenai peningkatan mutu genetik dan pengembangan program pelestarian kerbau Gayo secara berkelanjutan untuk menjaga keberlangsungan pertumbuhan populasi salah satu plasma nutfah nasional. Penelitian ini dilaksanakan di Kabupaten Gayo Lues meliputi dua kecamatan yaitu Blangkejeren dan Dabun Gelang. Penelitian ini menggunakan metode kualitatif dengan melakukan survei secara simple random sampling terhadap 54 peternak kerbau. Jumlah sampel ditentukan dengan rumus Slovin dan kriteria peternak memelihara minimal 5 ekor ternak kerbau. Data hasil penelitian diolah dengan menghitung persentase lalu dibandingkan dengan standar yang ditetapkan Peraturan Menteri Pertanian (2006). Hasil penelitian menunjukkan bahwa skor penerapan aspek teknis pemeliharaan ternak kerbau yang diperoleh di Kabupaten Gayo Lues adalah 55,96% diantaranya penerapan aspek teknis pemuliaan dan reproduksi 62,39%, makanan 41,47%, tatalaksana pemeliharaan 57,20%, kesehatan 61,71%, dan kandang dan peralatan 73,40%. Hal tersebut dapat disimpulkan bahwa penerapan aspek teknis pemeliharaan kerbau di Kabupaten Gayo Lues masih belum cukup baik.